Ranking of occupational health and safety risks by a multi-criteria perspective: Inclusion of human factors and application of VIKOR. (June 2021) - La Fata, C.M.; Giallanza, A.; Micale, R.; La Scalia, G.
Highlights: Proposal of a structured MCDM-based approach to prioritize occupational risks. Inclusion of human error probability as evaluation criterion. Extension of HEART and SPAR-H in manufacturing SMEs, also including human performance factors dependencies. Application to a real case. Abstract: Nowadays, the Occupational Health and Safety (OHS) is more and more recognized as a crucial process to be properly managed and continuously improved by every organization. Primarily addressed to prevent workers' injuries and diseases, it positively impacts on productivity, competitiveness and reputation as well as it contributes to cost savings in general. OHS management is grounded upon the risk assessment results, on the basis of which defining corrective measures to be taken to reduce risks to acceptable values. In this regard, the paper proposes a Multi-Criteria Decision Making (MCDM) based methodology addressed to the occupational risks prioritization. In order to overcome the shortcomings of the traditional risk matrix, the new methodology considers three evaluation criteria differently weighted by the Analytic Hierarchy Process (AHP) method. Among criteria, one specifically refers to the contribution of human factors to the occurrence of accidents, and a combination of Human Error Assessment and Reduction Technique (HEART) and Standardized Plant Analysis Risk-Human (SPAR-H) techniques is used to this aim. Afterwards, the Vlse Kriterijumska Optimizacija Kompromisno Resenje (VIKOR) method is applied to rank risks. The proposed approach is implemented in a Sicilian manufacturing company that produces and commercializes wooden products, together with the sale of outdoor furniture. The comparison of the obtained results with the ones arising from previous risk analyses performed by the company highlights the higher ability of the proposed methodology to differentiate risks.